If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2(2x + 7) = -5 + 5x Reorder the terms: -2(7 + 2x) = -5 + 5x (7 * -2 + 2x * -2) = -5 + 5x (-14 + -4x) = -5 + 5x Solving -14 + -4x = -5 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. -14 + -4x + -5x = -5 + 5x + -5x Combine like terms: -4x + -5x = -9x -14 + -9x = -5 + 5x + -5x Combine like terms: 5x + -5x = 0 -14 + -9x = -5 + 0 -14 + -9x = -5 Add '14' to each side of the equation. -14 + 14 + -9x = -5 + 14 Combine like terms: -14 + 14 = 0 0 + -9x = -5 + 14 -9x = -5 + 14 Combine like terms: -5 + 14 = 9 -9x = 9 Divide each side by '-9'. x = -1 Simplifying x = -1
| 3a+4(a+16)= | | 4.04=0.014x^2+0.89 | | 0.03x+.04(18000-x)=560 | | 9+3x-2= | | -p+4=25-8p | | 12.5m=32 | | m^2+49=0 | | 2p+p=90 | | 2x/3=5x-10/5 | | y-3.8y-6=-1.9y-11.4 | | 12x^2=77 | | (7-v)(4v-2)=0 | | 3(c+2)+1=5c-1 | | x^2+x=1.52 | | 509.8104=2*3.14*r^2+2*3.14*r*55.6 | | -7(-5k-7)=84 | | 5(k-3)=(k-5) | | (7x-15)1/3 | | 6(5/9) | | F(x)=(-6)+3 | | -1+20n+15=8n-10+6 | | 70-a=25 | | .05x+09(28000-x)=2400 | | -2+b=3 | | 52x=1/625x | | q=50-2p | | -1+20n+3=8n-10+6 | | 2y+3x+1=0 | | 9=-r | | 12x^2-6x=45 | | b+8b+1=19 | | 0=16t^2-40t-25 |